Vacuolar-type proton ATPase is required for maintenance of apicobasal polarity of embryonic visceral endoderm - Ge-Hong Sun-Wada (Nature Portfolio, 2021)
Abstract The endocytic compartments keep their interior acidic through the inward flow of protons and anions from the cytosol. Acidification is mediated by a proton pump known as vacuolar-type ATPase (V-ATPase) and transporters conferring anion conductance to the organellar membrane. In this study, we analysed the phenotype of mouse embryos lacking the V-ATPase c-subunit. The mutant embryos differentiated embryonic epithelial tissues, primitive endoderm, epiblast, and extraembryonic ectoderm; however, the organisation of these epithelia was severely affected. The apical-basal polarity in the visceral endoderm layer was not properly established in the mutant embryos, resulting in abnormal epithelial morphology. Thus, the function of V-ATPase is imperative for the establishment and/or maintenance of epithelial cell polarity, which is required for early embryogenesis.